Tinjauan Penerapan Rekam Medis Elektronik (Metode PIECES) terhadap Efektivitas Tenaga Medis di Rumah Sakit X - Riko Maulana Yusuf; Yuyun Yunengsih (Jurnal Infokes, 2026)
This study aims to evaluate the effectiveness of the implementation of Electronic Medical Records (EMR) in Hospital X using the PIECES method (Performance, Information, Economy, Control, Efficiency, Service). This evaluation is important to support the hospital's digital transformation and improve the work efficiency of medical personnel. The research was conducted using a qualitative-descriptive approach through in-depth interviews and observations of 12 medical record officers who have used EMR for at least two years. The results showed that EMR has a positive impact in improving service speed, recording efficiency, and accuracy of medical information. The system is quite stable and able to save the use of paper, as well as speed up the service process. However, there are still some specific problems, such as system latency during peak hours, duplication of ICD codes, inter-officer account borrowing that poses data security risks, and technical infrastructure limitations such as hardware and networks. As a recommendation, this study recommends increasing the capacity of network and server infrastructure, periodic user training, enforcing system access security policies, and systematic and periodic evaluation based on PIECES indicators to ensure the sustainability and optimisation of EMR in the future.